Relationship between parental role and gadget addiction in early childhood - Haryati, Tati; Suparman, Suparman; Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
According to Handrianto (2013) the use of gadgets in children has positive and negative impacts, as well as in early childhood. The positive impacts of using gadgets on children include developing imagination, training children's intelligence, increasing children's self-confidence, developing reading, mathematics and problem solving skills. Meanwhile, the negative impacts of using gadgets are reducing concentration in studying, laziness in writing and reading, decreased social skills, addiction, can cause health problems, hinder children's cognitive development, hinder language skills and affect children's behavior.Parents are expected to have a big role in preventing the negative impact of gadget use in early childhood. For this reason, parents need to be given socialization about the role of parents in preventing early childhood addiction to gadgets. This research has two objectives, firstly to find out the positive relationship between the role of parents and gadget addiction in older people and secondly to find out the negative relationship between the role of parents and gadget addiction in young children.The research method used is quantitative research using Spearman Rank Correlation Analysis from the results of a questionnaire on the role of parents and parents' perceptions about gadget addiction in early childhood. Parents were divided into two groups, 1 group that was not given socialization and 1 group of parents who were given socialization. Both groups were given a pre-test and post-test. This research was carried out on TKIT Taamasa parents who were selected using a purposive sampling technique.Based on research conducted on TKIT Taamasa parents, the Spearman Rank correlation coefficient test results obtained from the pre-test results in the control group were -0.449 (negative). Likewise, the results of the correlation coefficient test for the control group post test were -0.389 (negative), the experimental group pre test results -0.114 (negative) and the experimental group post test -0.141 (negative). This shows that there is a negative relationship between the role of parents and gadget addiction in early childhood. The higher the role of parents, the lower the gadget addiction in young children. The negative coefficient value also proves that there is no positive relationship between the role of parents and gadget addiction in early childhood.Based on the research results, it was found that there was a negative relationship between the role of TKIT Taamasa parents and gadget addiction in early childhood in the group of parents who were given socialization and who were not given socialization regarding the role of parents in gadget addiction in early childhood. The higher the role of parents, the lower the addiction to gadgets in early childhood. Thus, researchers suggest that the role of people needs to be increased to prevent early childhood addiction to gadgets.